Intelligence, academic achievement, and pediatric injury among a large sample of kindergartners (Italian Journal of Public Health, 2010)
Objectives: Previous work reports mixed results on the roles of intelligence and academic achievement on child injury risk. Some early research offered evidence of links between lower levels of intelligence and higher rates of pediatric injury, but other work has suggested there is no relation between the variables. This study investigated the matter further, in the context of a large sample and with strong statistical power.Methods: Data from a national sample of 8002 kindergartners in the United States, all from low-income families, were analyzed. Intelligence was estimated using the Peabody Picture Vocabulary Test-Revised and academic achievement with the Reading and Mathematics scales of the Woodcock Johnson Psycho- Educational Battery-Revised. Mothers reported whether children had experienced an injury in the previous year that required professional medical attention.Results: Results of both bivariate and multivariate ordinal logistic regression models suggest higher levels of reading achievement and of mathematics achievement were associated with slightly reduced risk of pediatric injury. Intelligence was not related to injury history.Conclusions: Academic achievement, but not intelligence, appears to relate in a small but statistically significant inverse manner with risk for pediatric injury among kindergartners from a low-income background. Possible mediators include children’s ability to learn and remember safety-related rules or the fact that parents who encourage learning in the household might also safeguard children more effectively.
Keywords: Injury; safety; intelligence; academic achievement; kindergartners